2012
DOI: 10.1589/jpts.24.169
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cold Stimulation of the Dermatome Modulates Activation of the Quadriceps

Abstract: Abstract. [Purpose] To examine electromyographic (EMG) activity change during dynamic contraction of the quadriceps with skin cold stimulation (SCS) over the vastus lateralis (VL) and L4 dermatome area on the medial side of the lower leg. [Subjects and Methods] Seventeen healthy male volunteers participated. Dynamic knee extension was performed at 15% maximum voluntary contraction (MVC). SCS is a method used to cool the skin to 25 °C using a gel-cooling pad. The SCS method has no effect on the muscle below th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Other researchers have reported that HT-MUs were facilitated by cutaneous afferent input Wuerker et al 1965). Moreover, our previous results support the findings of other researchers, suggesting that MNs of the vastus lateralis muscle can be modulated through skin cooling of the relevant spinal segment (Sugawara et al 2012). We suggested that the change in MU activation pattern due to skin cooling may be a response to facilitation of the superficial or deeper regions of the muscle.…”
Section: Introductionsupporting
confidence: 90%
“…Other researchers have reported that HT-MUs were facilitated by cutaneous afferent input Wuerker et al 1965). Moreover, our previous results support the findings of other researchers, suggesting that MNs of the vastus lateralis muscle can be modulated through skin cooling of the relevant spinal segment (Sugawara et al 2012). We suggested that the change in MU activation pattern due to skin cooling may be a response to facilitation of the superficial or deeper regions of the muscle.…”
Section: Introductionsupporting
confidence: 90%
“…SC at 25 °C during a slow ramp contraction also changes MU recruitment pattern and selectively induces large MU recruitment [ 12 ]. Furthermore, in practical rehabilitation trials, recent studies have shown that maintaining the skin temperature at around 25 °C, using a gel-cooling pad on the quadriceps muscle, enhances muscle activity at 15% maximum voluntary contraction (MVC) [ 13 ] and improves the rate of force development (RFD) in the early phase of contraction [ 14 ]. On the basis of these studies, it is presumed that maintaining the skin temperature at 25 °C is appropriate for modulating MN excitability without a reduction in the muscle temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that facilitatory and inhibitory responses of spinal motor neurons (MNs) occur with electrical stimulation of cutaneous nerves (Burke et al 1989;Marchand-Pauvert et al 2002), skin brushing (Mason 1985;Wood et al 1998;Sugawara et al 2013), skin anesthesia (Sabbahi and De Luca 1981;Delwaide and Crenna 1984;Arsenault et al 1993), and skin cooling (Yona 1997;Sugawara et al 2012;Shimose et al 2014). Modulation of the MN pool differs depending on the type of stimulation and Hagbarth (1960) suggests that the motor response to noxious stimulation of the skin is either facilitative or inhibitory due to interaction of the skin with homogenous muscle.…”
Section: Introductionmentioning
confidence: 99%